Enlace covalente - Izquierdo Vega, Elizabeth (2019)
The area of science and technology, are present in different contexts of human activity and occupy an important place in the development of knowledge and culture of our societies that have been transforming our conceptions about the universe and our ways of life. This context requires citizens who are able to question themselves, look for reliable information, systematize it, analyze it, explain it and make decisions based on scientific knowledge, and considering the social and environmental implications. It also requires citizens who use scientific knowledge to constantly learn and have a way of understanding the phenomena that happen around them._x000D_ The achievement of the graduation Profile of Basic Education students requires the development of various skills. Through the approach of research and scientific and technological literacy, Science and Technology area promotes and facilitates students to develop the following skills._x000D_ • Explain the physical world based on knowledge about living beings, matter, energy,_x000D_ biodiversity, Earth and universe._x000D_ • Design and build technological solutions to solve problems in its environment._x000D_ With the topic covalent bond we will get our students to know that everything that exists around us is linked by atoms to form chemical compounds.